2021
DOI: 10.1016/j.ijscr.2021.106096
|View full text |Cite
|
Sign up to set email alerts
|

Iliac-femoral stent-graft infection after hybrid procedure redo: Case report

Abstract: Introduction Stent-graft infection in peripheral arteries is rare and potentially dangerous. The use of hybrid procedures, in complicated patients previously treated, involves an increase of infective risk especially in no collaborative patients. Presentation of case We report a case of rare stent-graft infection in a patient treated for a Rutherford IV Multiple Peripheral Arterial Disease (MPAD) involving the right iliac-femoral axis with stenosis on deep femoral arter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…About a review of the literature, of the 49 reported cases of brachial artery aneurysm secondary arteriovenous fistula ligation, saphenous vein inverted was used in 21 patients (42.8 %), PTFE prostheses in 9 patients (18.4 %), cephalic vein or basilic vein inverted in 3 patients (6.2 %), other surgeries in 16 patients (32.6 %) ( Table 2 ). In our experience the bypass in PTFE was complicated by an infection probably due to the lack of tissues necessary to protect a graft positioned less deeply than the skin, but in absence of adequate vein grafts for replacement, PTFE is a valid option [ [23] , [24] , [25] , [26] ].…”
Section: Clinical Discussionmentioning
confidence: 99%
“…About a review of the literature, of the 49 reported cases of brachial artery aneurysm secondary arteriovenous fistula ligation, saphenous vein inverted was used in 21 patients (42.8 %), PTFE prostheses in 9 patients (18.4 %), cephalic vein or basilic vein inverted in 3 patients (6.2 %), other surgeries in 16 patients (32.6 %) ( Table 2 ). In our experience the bypass in PTFE was complicated by an infection probably due to the lack of tissues necessary to protect a graft positioned less deeply than the skin, but in absence of adequate vein grafts for replacement, PTFE is a valid option [ [23] , [24] , [25] , [26] ].…”
Section: Clinical Discussionmentioning
confidence: 99%
“…Such interventions aim to increase the blood flow to the foot, which in turn, enhances cutaneous oxygen pressure, promoting infection clearance and ulcer granulation [ 34 , 35 , 36 ]. Patients affected by diabetic artery disease often evolve toward critical limb-threatening ischemia (CLTI), with a multilevel arterial involvement (multilevel peripheral artery disease—MPAD) of up to 90% [ 37 , 38 , 39 ]. To achieve consistent clinical improvements, these patients require extensive multilevel reconstruction [ 40 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%